Innovations in bioethanol production: A comprehensive review of feedstock generations and technology advances - Abeer Kazmi; Tahira Sultana; Amir Ali; Aneela Nijabat; Gaojie Li; Hongwei Hou (Energy Strategy Reviews)
To switch to renewable energy sources from fossil fuels, there is an urgent global need for an inventive technique for turning food waste into biofuels. The production of bioethanol from food waste might result in a long-lasting method that would satisfy both the growing population's energy needs and the problem of disposing of food waste. According to estimates, one-third of the food produced worldwide, or 1.3 billion tonnes annually, is wasted. Biofuels like bioethanol reduce dependency on fossil fuels and can operate with a fleet of internal combustion engines. Using biofuels can decrease carbon dioxide emissions from internal combustion engine fleets. Typically, bioethanol production involves the microbial fermentation of fermentable carbohydrates into ethanol. Fermentation processes used in bioethanol production generally employ yeast (Saccharomyces cerevisiae) to convert sugars from biomass into ethanol and CO2. Batch, fed-batch, and continuous fermentation techniques are used, with advances such as immobilized cell reactors and genetic engineering improving output and efficiency. Furthermore, combining enzymatic hydrolysis with fermentation (simultaneous saccharification and fermentation) enhances the conversion of complex carbohydrates to ethanol. Traditional feedstocks (first-generation feedstock) consist of cereal grains, sugar cane, and sugar beets. However, lignocellulosic (second-generation), microbial biomass (third-generation), and genetically modified microalgae (fourth-generation) based feedstocks have been researched due to concerns about the sustainability of food. This paper discusses available methods, such as fermentation techniques, and compares bioethanol generation from various feedstocks. The objectives of this review are to compare different generations of biofuel production. The current review also provides industrial producers with knowledge of the technologies and resources that are currently accessible and the possibilities for future innovation.